Proceedings of the 2015 International Forum on Energy, Environment Science and Materials 2015
DOI: 10.2991/ifeesm-15.2015.282
|View full text |Cite
|
Sign up to set email alerts
|

Desilting Laws of Precipitation Washout Test in Xiaolangdi Reservoir

Abstract: Precipitation washout is a common and effective measure to restore the storage capacity of reservoir. In order to study erosion effects under the condition of different boundary conditions, control water level and flood duration in later sediment retaining period of Xiaolangdi Reservoir flood duration, four groups of precipitation washout tests were conducted. The paper analyzes reservoir erosion effects of the different group. In this paper, the result show that, with more discharge and sediment, lower water … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…During the process of pipeline layout, an adverse slope section will appear due to the influence of the dam body. Wang [17] found that in the reverse slope section of a reservoir self-priming pipeline, because the sinking direction of the heavy solid material moves in the opposite direction of flow, it is often the portion part that has a high occurrence of pipe plugging. If the sediment in the reservoir has been silted for a long time, the sediment is a severe concretion [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…During the process of pipeline layout, an adverse slope section will appear due to the influence of the dam body. Wang [17] found that in the reverse slope section of a reservoir self-priming pipeline, because the sinking direction of the heavy solid material moves in the opposite direction of flow, it is often the portion part that has a high occurrence of pipe plugging. If the sediment in the reservoir has been silted for a long time, the sediment is a severe concretion [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%